2022
DOI: 10.1016/j.jesf.2021.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between waist circumference and cardiorespiratory fitness in Chinese children and adolescents: Results from a cross-sectional survey

Abstract: Background This article assessed the relationship between waist circumference (WC) and cardiorespiratory fitness (CRF) of children and adolescents aged 7–18 years. Methods Using a stratified cluster random sampling method, 92,574 children and adolescents (47,364 males and 45,210 females) were extracted. CRF was measured by performance in the 20 m shuttle run test (20mSRT) and the subsequent estimation of maximal oxygen consumption ( O 2max … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…We found an inverse U-shape association between FVC and BMI, with overnutrition and undernutrition students having worse FVC levels than normal-weight students. Studies have indicated that excessive accumulation of fat can change its mechanical action on the thoracic and abdominal cavity, resulting in changes in FVC and respiratory regulation, thus impairing lung function levels [35]. Similar inverse U-shapes were also found between BMI or waist circumference and cardiorespiratory fitness in Chinese children and adolescents [36].…”
Section: Discussionmentioning
confidence: 67%
“…We found an inverse U-shape association between FVC and BMI, with overnutrition and undernutrition students having worse FVC levels than normal-weight students. Studies have indicated that excessive accumulation of fat can change its mechanical action on the thoracic and abdominal cavity, resulting in changes in FVC and respiratory regulation, thus impairing lung function levels [35]. Similar inverse U-shapes were also found between BMI or waist circumference and cardiorespiratory fitness in Chinese children and adolescents [36].…”
Section: Discussionmentioning
confidence: 67%
“…Waist circumference was categorized according to percentile by the Lambda Mu Sigma (LMS): very low (WC < 15th percentile), normal (15th percentile ≤ WC < 85th percentile), high (WC ≥ 85th percentile) ( 38 ). Many studies have demonstrated that EF could be affected by obesity rate ( 22 , 23 ), dietary intake ( 39 ), physical activity ( 40 ), and maximum oxygen uptake (VO 2max ) ( 41 ).…”
Section: Methodsmentioning
confidence: 99%
“…Based on Model 1, Model 2 controlled for MVPA, VO 2max . Physical activity status was obtained by the following two questions: “In the past 7 days, how many times did you have MVPA on school days and weekends, respectively?” If students answered more than 0 times, they were further asked about the duration each time, “On average, how long does each activity last?” The VO 2max was estimated by 20 m SRT and the details measurement of 20 m SRT was provided in our previous study ( 38 ). Based upon Model 2, Model 3 included breakfast, sugar-sweetened beverage intake as additional variables.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the past, studies on the physical fitness of children and adolescents often used a certain physical fitness project for research, which could not fully reflect the physical fitness level of children and adolescents, so there were certain limitations [ 5 , 6 , 7 ]. For example, a study analyzed the relationship between cardiorespiratory fitness and waist circumference in Chinese children and adolescents; cardiorespiratory fitness was measured by 20 m shuttle run test, and the analysis showed that the relationship between cardiorespiratory fitness and waist circumference showed an inverted “U” curve [ 8 ]. With the deepening of research, in recent years, the use of physical fitness index (PFI), which comprehensively reflects the level of physical fitness, has gradually increased, and the relationship between physical fitness index and health has been deeply analyzed [ 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%